Passando a boiada : enquadramentos do governo antiambientalista de Jair Bolsonaro nos editoriais dos jornais Folha de S. Paulo e Estado de S. Paulo - Campos, Fernanda Safira Soares (2023)
Environmental policies were negatively affected in various aspects throughout the mandate of the far-right president, Jair Bolsonaro (2019-2022), attracting attention from the national media and various international actors and organizations concerned about the denialist discourse and actions to dismantle the environmental agenda carried out by the president. In light of this, this research aims to analyze the editorial coverage of the newspapers O Estado de S. Paulo and Folha de S. Paulo to understand how both outlets positioned themselves in relation to the environmental agenda of the Bolsonaro government. We start from the following research problem: "How did the editorial coverage of the newspapers O Estado de S. Paulo and Folha de S. Paulo frame the environmental agenda during Jair Bolsonaro's government?" Empirically, the study has a corpus composed of 53 editorials from Folha de S. Paulo and 111 editorials from O Estado de S. Paulo, published between 2019 and December 2021. To answer our objectives, the collected editorials were initially subjected to a lexical analysis using the software Iramuteq to identify the prevailing semantic cores in both newspapers, followed by a quantitative and qualitative framing analysis based on the categories proposed by Robert Entman (1993). In theoretical terms, the dissertation addresses the relationship between power and the environment, with emphasis on the social, political, and economic factors that influence environmental policies, the role of the media in presenting and discussing these issues, as well as the position of editorials in journalistic practice and the concept of populism for understanding the policies and ideology of former President Jair Bolsonaro. The results indicate the adoption of different framings in both newspapers. While O Estado de S. Paulo places greater emphasis on the negative economic impacts on agribusiness, Folha de S. Paulo highlights the worsening of environmental damages, such as wildfires and illegal deforestation.